Technical Efficiency among Small and Medium Scale Entrepreneurs in High Quality Cassava Flour In Four Geo-Political Zones of Nigeria - Ayoola, Josephine Bosede; Dzever, Donald Denen; Alakali, Joseph; Sanni, Lateef; Ngadi, Michael; Kok, Robert (International Journal of Economics, 2016)
Purpose: Inadequate empirical data on value addition to cassava processed might be the bane of the inability of the enterprise to attract the necessary attention of private entrepreneurs in the sector. Therefore this study was carried out to analyze technical efficiency among small and medium scale entrepreneurs (SMEs) in high quality cassava flour (HQCF) processing in Nigeria. Methodology: Multi-staged purposive and random sampling techniques were used in selecting 104 SMEs from four out of six existing geopolitical zones. Data collected using structured questionnaires and interview schedule were analyzed using descriptive statistics and stochastic frontier production function. Results: The results revealed that the coefficients for cassava tuber and capital were significant and positively influence HQCF processing at 5 percent level of probability. Household size and access to credit were negatively and significantly related to technical efficiency at 5 percent level of probability; while gender and processing experience were positively related to technical efficiency at 5 percent and 1 percent levels of probability respectively. The average technical efficiency of 79 percent implies that HQCF processors could further increase the efficiency of resource utilization by 21 percent. Recommendation: It was therefore recommended that policy measures should aim at delivery of supervised credit to processors, skill development especially for women, expanded production of raw cassava and enhanced capital base in form of appropriate machineries for processing HQCF.